PERANCANGAN DAN SIMULASI PLTS ATAP 1 KWP MENGGUNAKAN HELIOSCOPE - Civavisna Brahma, I Gede; Satya Kumara, I Nyoman; Dwi Giriantari, Ida Ayu (Jurnal SPEKTRUM; Vol 8 No 2 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i02.p28, 2021)
Solar Power Plant (PLTS) as one of the renewable energy sources that is being focused on its development. This article discusses the design and simulation of the performance of a 1 kWp rooftop solar power plant using a Helisocope. The input data required by the Helioscope is PLTS technical specifications such as solar panel technology, inverter type, number and type of modules selected and land area. The location data required by the PLTS system includes the coordinates, the type of roof of the building, the environment around the PLTS and meteorological data. The 1 kWp PLTS roof system designed at the location that the author uses uses 7 pcs Canadian Solar 195 Wp panels, 1 pcs 1 kW AEC inverter, installed on the roof of the building facing north, and connected to the PLN network via a net meter. This 1 kWp rooftop PLTS is capable of producing an average daily average of 5,48 kWh, 41,07 kWh weekly, 164,29 kWh monthly, and annual 1971,5 kWh. Energy production varies by an average of 8% per month with the minimum production in January of 135,1 kWh and the highest in July of 184,5 kWh. The designed 1 kWp PLTS roof produces a performance ratio of 73,6% with the irradiation received in a year reaching 1859,2 kWh/m2. The initial investment required to build a 1 kwp PLTS roof is IDR. 20.000.000.